Re-envisioning a traditional liaison library model to accommodate the digital scholarship needs of users - Heyns, Erla P. (Qualitative and Quantitative Methods in Libraries, 2019)
The focus of this paper is a case study of the liaison model at the Humanities, Social Science and Education Library at Purdue University. In order to fully integrate new digital scholarship services into the library it became apparent that a re-envisioning of the current liaison model was required.